PERANAN PENDIDIKAN LUAR SEKOLAH DALAM PEMBANGUNAN SUMBER DAYA MANUSIA - Nur Agustiningsih, Satriyo Pamungkas (Istoria: Jurnal Ilmiah Pendidikan Sejarah Universitas Batanghari, 2017)
Abstrac               The purpose of this research is to describe the types of out of school education and to know the role of out of school education in building human resources. The method in this research is library research by doing analysis to scientific journals and other literatures then do drawing conclusion. The results showed that (1) Out of school education consists of two educational frame, namely non-formal and informal education. (2) Out of school education has a basic role as an addition, supplementary and substitute for school education. As a substitute for school education, out of school education can replace formal education frame which, for some reason, do not follow formal education. As a school-based supplement, out of school education is undertaken to increase the knowledge, skills that are lacking in school education. As complement of school education, and as a complement the knowledge and skills that are lacking or not obtained in schools.Keywords: Out of school education, Human Resources